ADINA - Hürden und Treiber für die Umsetzung innovativer Automatisierungstechnik und Ergonomieunterstützung der Intralogistik - Tim Gruchmann; Kristina Nestler; Alexander Brauckmann; Julian Schneider; Carsten Fischer; Andreas Hecht (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2018)
– Logistics commands a huge variety of dynamic developments, driven by technological, organizational as well as market changes. In particular automation and ergonomics is seen as promising trends to tackle potentials for economical, eco-logical and social sustainability. The publication of this research paper marks the first, explorative phase of the project 'ADINA', which does encompass the development of innovative warehousing and picking strategies. While the main focus of the project work is to increase competitiveness of the participating companies, the present contribution follows a case study approach to explore drivers and barriers of implementing automation and ergonomics solutions in intralogistics processes. The paper is structured as follows: Section 1 introduces the project aim, while section 2 and 3 deal with work environments in logistics and a specific focus on ergonomics in these work environments. Section 4 provides a brief summary of the applied methodological approach of case study research, expert interviews and evaluation. Section 5 and 6 present the findings of the within- and cross-case analysis, while finally section 7 provides an outline of upcoming milestones in the project ADINA.
Keywords: 650